2002
DOI: 10.1056/nejmoa020245
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Risk of Heart Failure

Abstract: In our large, community-based sample, increased body-mass index was associated with an increased risk of heart failure. Given the high prevalence of obesity in the United States, strategies to promote optimal body weight may reduce the population burden of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
998
3
25

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,533 publications
(1,095 citation statements)
references
References 30 publications
30
998
3
25
Order By: Relevance
“…Those factors are well known to predict incident cardiovascular disease,22, 23, 24 and our study uniquely demonstrated that the status of these factors at middle age would have prognostic value for prognosis after incident MI as well. In our study, healthy diet and physical activity at baseline were not individually associated with adverse outcomes after incident MI.…”
Section: Discussionsupporting
confidence: 61%
“…Those factors are well known to predict incident cardiovascular disease,22, 23, 24 and our study uniquely demonstrated that the status of these factors at middle age would have prognostic value for prognosis after incident MI as well. In our study, healthy diet and physical activity at baseline were not individually associated with adverse outcomes after incident MI.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, it is critical to note that these results do not negate the importance of BMI in standard risk prediction. Obesity is a well‐established marker of increased CVD risk,1 although these results suggest that it does not fully explain CVD risk. Ultimately, these results suggest that a “life‐course” approach to risk assessment that begins early and integrates BMI, known risk factors (eg, waist circumference), and metabolic risk will be critical in halting CVD progression.…”
Section: Discussionmentioning
confidence: 96%
“…Metabolic syndrome is a well‐established risk factor for cardiovascular disease (CVD), including coronary artery disease and heart failure 1. Alterations in metabolic risk linked to CVD may develop over decades before clinical CVD 2, 3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated body mass index (BMI; kg/m 2 ) is a recognized risk factor for new‐onset HFrEF and HFpEF 108, 109, 110, 111. Obesity has been associated with LVH and incipient LV dysfunction 112, 113.…”
Section: Obesity Phenotypementioning
confidence: 99%